2021
DOI: 10.1155/2021/6672525
|View full text |Cite
|
Sign up to set email alerts
|

Different Doses of β‐Cryptoxanthin May Secure the Retina from Photooxidative Injury Resulted from Common LED Sources

Abstract: Retinal damage associated with loss of photoreceptors is a hallmark of eye diseases such as age-related macular degeneration (AMD) and diabetic retinopathy. Potent nutritional antioxidants were previously shown to abate the degenerative process in AMD. β-Cryptoxanthin (BCX) is an essential dietary carotenoid with antioxidant, anti-inflammatory, and provitamin A activity. It is a potential candidate for developing intervention strategies to delay the development/progression of AMD. In the current study, the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 69 publications
3
11
0
Order By: Relevance
“…The beneficial role of BCX has been reported in different animal studies. In this line, this carotenoid administered orally (2 and 4 mg/kg) protected the retina against light-induced damage through an increase in antioxidant status as well as a reduction in NF-κB levels and the subsequent production of IL-1β and IL-6 [304]. As regards metabolic disorders, the antiobesity properties of dietary BCX for 12 weeks have been reported in a mouse model of high-fat diet-induced insulin resistance.…”
Section: β-Cryptoxanthin 461 In Vivo Studiesmentioning
confidence: 91%
“…The beneficial role of BCX has been reported in different animal studies. In this line, this carotenoid administered orally (2 and 4 mg/kg) protected the retina against light-induced damage through an increase in antioxidant status as well as a reduction in NF-κB levels and the subsequent production of IL-1β and IL-6 [304]. As regards metabolic disorders, the antiobesity properties of dietary BCX for 12 weeks have been reported in a mouse model of high-fat diet-induced insulin resistance.…”
Section: β-Cryptoxanthin 461 In Vivo Studiesmentioning
confidence: 91%
“…It reduced the oxidative and mitochondrial stress markers and ameliorated retinal thickness. Furthermore, it also alleviated inflammatory and apoptotic markers to prevent retinal degeneration [309]. KIOM-79, an 80% ethanolic extract prepared from Glycyrrhiza root, pueraria root, Euphorbia root, and Magnolia bark.…”
Section: Formulationsmentioning
confidence: 99%
“…58,64 Although cryptoxanthin is not involving in the macular pigment, it played a similar role in reducing photochemical and photooxidative retinal injury. 65 Based on such a possible molecular mechanism, previous studies have shown that these carotenoid components have neuroprotective effects and are associated with eye diseases, particularly macular degeneration. 44,47 Based on such a possible molecular mechanism, clinical researchers have identified the associations between eye diseases and the sleep-related symptoms in affected populations, suggesting that eye diseases, especially macular disease, might play an intermediary role between circulating carotenoid levels and the risk of sleep disorders.…”
Section: Papermentioning
confidence: 99%